ANALISIS MODEL MANAJEMEN PERMINTAAN SCM NETWORK DAN PERAMALAN PERMINTAAN PADA PENJUALAN BUSANA MUSLIM MENGGUNAKAN METODE LINEAR REGRESSION - Vela Maghfiroh; Yusuf Amrozi; Qushoyyi Bondan Prakoso; Mochamad Adam Aliansyah (METHOMIKA: Jurnal Manajemen Informatika & Komputerisasi Akuntansi, 2021)
Supply chain management is very important for a company because it will affect supply performance in the company. Doing business in this era has many challenges that must be faced, especially in the Muslim clothing business. The way to stabilize the demand diagram of the Muslim clothing business, retailers are required to manage the supply chain so that they can meet the total demand. The object of this research is Rabbani Cirebon which was obtained from a literature study published in a journal entitled "Trend of Muslim Lifestyle Changes" from Banjarmasin State Polytechnic. The journal has sales data based on product types from monthly in 2016. From this data will be processed and analyzed using data analysis techniques. This data analysis technique uses time series forecasting data analysis techniques. From this time series method, this research uses moving average and linear regression. After modeling the data, the forecast error is measured using MAD, MAPE, RMSE, and MSE. The overall MSE results were 103731.8 and RMSE 322.0743. The benefit of demand forecasting is to reduce the Bullwhip Effect, plan future resources, for example, such as stock management, place control, product distribution, and demand for raw materials so as to make the right decisions. The results showed that the linear regression method has better forecasting than the moving average because linear regression has a smaller error rate than the moving average. But even so, the error rate of this study is still very large, so it is necessary to do more research to minimize the error rate.